THE INFLUENCE OF STAKEHOLDER PRESSURE AND COMPANY ACTIVITIES ON SUSTAINABILITY REPORTS - Maya Arisandy; Erlina Sari Pohan; Ihsan Amrulloh; Muhammad Fahimi Bin Sofian; Paradila Dewi Yulia Ningrum (Amal Insani Foundation, 2026)
In Indonesia, sustainability reporting has shown an increase thanks to regulations that require companies to report on their social and environmental responsibilities. However, despite clear regulations, there are still a number of companies that have not fully fulfilled this obligation by presenting sustainability reports. Out of 46 companies, only 11 consistently publish sustainability reports. This shows that there are still many who have not met the standards despite increasing socio-environmental awareness and regulations. The purpose of this research is to examine the influence of stakeholder pressure and company activities on sustainability reports. Stakeholder pressure is the pressure exerted by public stakeholders who demand communication regarding corporate social responsibility activities in the form of reports, while the company's activities reflect the level of success and failure in implementing activities in accordance with the established policy programs. This research uses multiple linear regression methods with a sample size of 11 mining companies listed on the Indonesia Stock Exchange from 2018 to 2022, and the sampling technique employed is purposive sampling. This research shows that companies facing higher stakeholder pressure will improve the quality of their sustainability report disclosures, while high company activities do not affect the sustainability report, as these activities are not directly related to the disclosure of the sustainability report